The Role of Animosity, Religiosity, and Allocentrism in Shaping Purchase Intention through Ethnocentrism and Brand Image - Kusumawardani, Kunthi Afrilinda; Yolanda, Monica (Organizations and Markets in Emerging Economies, 2021)
With the long history of the relationship between Indonesia and China, various sentiments may arise and influence the consumer purchasing decision. This study aims to determine the impact of animosity towards China, religiosity, and allocentrism of the Indonesians on the intention to purchase Chinese brands smartphones, mediated by consumer ethnocentrism and brand image. This study has 215 valid responses and was carried out using SPSS 25. Structural Equation Modelling (SEM) was performed using AMOS 22. The results show that consumer ethnocentrism is significantly influenced by animosity, religiosity, and allocentrism. Brand image can mediate between consumer ethnocentrism and purchase intention. This study gives a better understanding of Indonesian consumer ethnocentrism with animosity towards China, religiosity, and allocentrism, which will affect the Chinese brand image and Indonesians’ intention to purchase the product.